Internationalization of Indian Bio-Technology Firms: Case Analysis of Biocon - Vyas, Himanshu (2009)
Rapid globalization of the World’s Economies and the advancement in the field of Research & Development has raised a fierce competition among international firms. In this Era, the firms are moving towards internationalization to remain ahead in the race. Internationalization has become a way to take competitive advantages & further advancement over business rivals. This dissertation examines some key issues related to Internationalization of Indian Biotechnology firms. By employing Case study approach, the dissertation investigates the important aspects that determine the characteristics of Indian Biotech firms’s internationalization process. The motivations which are involved & the foreign market entry strategies which are taken are analyzed from the theoretical context.